Improving lateral resolution of ambient electrostatic force microscopy by intermittent contact method. Issue 169 (12th February 2016) - Liu, Dongzi; Ding, Xidong; Xu, Honglei; Lin, Guocong; Chen, Dihu
ABSTRACT: Electrostatic force microscopy (EFM) including its derivative, Kelvin probe force microscopy, is widely used to investigate mesoscopic/nanoscopic conducting/semiconducting structures and electrical interactions. However, the resolution of EFM in ambient is largely limited by the applicable force-detection techniques. This work demonstrates that the lateral resolution of ambient EFM can be significantly improved using an intermittent contact method in conjunction with a resonant multi-frequency method for electrostatic force detection. A lateral resolution of sub-10 nm is obtained. The high-resolution contrast reflects the variation of surface potential in sample on a nanoscale. The mechanism, which is attributed to the decreased effective tip-sample distance, is elucidated by theoretical analysis. The newly developed technique can be easily integrated with existing techniques to herald the next generation of high-resolution probe techniques for various nanoscopic applications.